Sinonasal Melanoma: A Case Report and Literature Review. (31st January 2017) - Alves, I. S. S.; Berriel, L. G. S.; Alves, R. T.; Pinto, M. B.; Oliveira, C. F. P.; Cazzotto, A. C.; Moura, W. V.
Abstract : Purpose . Sinonasal malignant mucosal melanoma is a rare, aggressive tumour. Nasal obstruction and epistaxis are the most commonly reported symptoms, although symptomatology may develop late and be nonspecific, which tends to delay diagnosis, resulting in a poorer prognosis. Case Report . This report describes a 64-year-old male patient with nasal obstruction and epistaxis. Computed tomography of the facial sinuses revealed a large lesion in the right nasal cavity, with infiltration into the left cavity, ethmoidal cells, and erosion of the cribriform plate. Initial incisional biopsy revealed an undifferentiated carcinoma of the right maxillary sinus, staged as T4aN0M0. Induction chemotherapy was initiated with cisplatin and etoposide. Response to treatment was complete. The patient was then submitted to radiotherapy with concomitant cisplatin. Immunochemical analysis revealed positivity for vimentin, S100, and HMB-45 (human melanoma black 45), a result compatible with a diagnosis of malignant melanoma. Discussion . Due to the rarity of the tumour and the patient's complete response to chemotherapy and since no blackened lesion had been found at the previous exam, treatment was continued as planned. The patient remains healthy, with no metastasis or recurrence. He is currently being monitored by the clinical oncology team.